Strengthening the instructional leadership capacity of school principals to improve the quality of learning - Nurkolis; Harjito; Soedjono; Kusdiyanto Eko Prabowo; Afina Sulistyahati; Hana Tristiandari (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
This community service program aims to strengthen the instructional leadership capacity of school principals in Semarang Tengah District, Semarang City. Recognizing the crucial role of principals in improving the quality of education, the program focused on identifying specific challenges principals face in implementing effective instructional leadership and evaluating the impact of intervention strategies. The methodology used included a series of workshops and mentoring sessions designed to equip principals with practical skills. Pre- and post-test results showed a significant increase in understanding, from 32 to 75 percent. Participants widely stated that the material was very useful (79 percent) and expressed a high interest in implementing it in their respective schools (59 percent very interested, 34 percent interested). Eighty-five percent of participants indicated a need for ongoing support and mentoring to implement effectively. The output that has been produced from this service is a self-evaluation instrument for school principals in implementing instructional leadership. These findings emphasize the importance of instructional leadership for student achievement and school improvement. The program contributed to increased understanding and readiness for practice, with a clear demand for ongoing support. Recommendations include comprehensive training by the Education Office and continued collaborative learning through the Principal Working Group.